The Responses of Exogenous Enzymes (Multi-Enzymes) on the Productivity and Stage of Production of Broilers Fed Vegetable-sourced Diets - Abu-Tayyeb, M.; Jahan, I.; Hossain , M.A.; Hossain, M.M.; Akter, N.; Nath, B.K. (International Journal of Poultry Science, 2019)
Objective: This experimental study was conducted to investigate the effects of diets and enzyme supplementation on the live weight (LW), feed intake (FI), feed conversion ratio (FCR), viability, leg bone quality and meat yield traits of broilers. Materials and Methods: In a 2×2 factorial experiment, having two diet types [corn-soya meal (CSM) based and corn-wheat-soya (CWS) based] and two enzymes levels (with or without), Broiler chicks (n = 112; Ross308) were assigned to four dietary treatments (CSM-, CSM+, CWS- and CWS+) with four replicates, seven chicks per replicate in a CRD. The chicks were fed on the ready-made broiler diet up to 25 days, after that formulated diets were supplied the birds ad libitum up to 45 days. All the diets were iso-caloric and iso-nitrogenous in nature and supplemented with or without enzymes in mash form. Results: Data revealed that diets (CSM- and CWS-) had no significant effect (p>0.05) on the LW, FI and FCR of broilers but enzymes (CSM+ and CWS+) increased (p<0.5, p<0.01) the LW and FI on day 45. Enzyme, diet and their interaction had no influence (p>0.05) on the viability, latency-to-sit (LTS), gait-scoring (GS) and bone traits of broilers. Diet and their interaction had no influence (p>0.05) on the bone quality traits of broilers except for enzyme. The mineral concentration (Ca%) and other bone traits were increased (p<0.05) by enzymatic diets. The results of dressing percentage, drumstick weight, thigh weight, breast weight, wing weight, back weight, shank weight and neck weight percentage of broilers were unaffected (p>0.05) by enzyme, diet and their interaction. Enzyme and diet had no influence (p>0.05) over the breast weight but its interaction influenced (p<0.05) the breast weight (%) of birds. Giblet and back weights (%) were influenced (p<0.05) by the diet only. Conclusion: It could be concluded that broilers might respond positively to enzymatic diets at the later stage of production.